A simplified approach for predicting temperatures in insulated RC members exposed to standard fire. (September 2017) - Kodur, V.K.R.; Yu, B.; Solhmirzaei, R.
Abstract: Fire resistance of concrete structural members can be enhanced through the application of external fire insulation on the surfaces of concrete member. For evaluating fire resistance of such insulated RC members, temperatures in concrete and steel reinforcement are to be known. This paper develops a simplified approach for predicting cross-sectional temperatures in an insulated RC structural member exposed to standard fire. The approach is derived by replacing the insulation layer into an equivalent concrete thickness layer and then undertaking statistical regression analysis on temperature data of modified concrete section. The effect of critical parameters, including geometry of concrete member and insulation, thermal properties of concrete and fire insulation, and duration of fire exposure is accounted for in temperature equations. The validity of the approach is established by comparing predictions from the proposed equation with data generated from fire tests and finite element analysis. These comparisons show the proposed equation gives reasonable prediction of temperatures, within a range of ±10%, in insulated concrete members. The applicability of the proposed approach in design situations is illustrated though a numerical example. The simplicity of the proposed method makes it attractive for use in design situations and for incorporation in design manuals. Highlights: An approach for predicting temperatures in insulated RC members is developed. Expression for equating insulation into an equivalent concrete thickness is derived. Applicability of the approach in design situations is illustrated though an example.